2020
DOI: 10.21037/gs.2020.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of two surgical methods on the secondary hyperparathyroidism

Abstract: Background: This study aimed to investigate the clinical efficacy of two surgical methods on hyperparathyroidism secondary to uremia and summarize the advantages and disadvantages of both methods.Methods: Uremic patients who received parathyroidectomy (PTX) in the last 3 years were divided into two groups according to the surgical methods used [subtotal parathyroidectomy (SPTX) group and total parathyroidectomy + autologous implantation (TPTX + AT) group]. TPTX was performed if less than 4 glands were found du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In contrast, parathyroidectomy is an effective method for long-term control, significantly lowering PTH levels into the normal laboratory reference range (<65 pg/mL) in 90%-100% of patients. 10,11 However, parathyroidectomy is typically reserved for patients with refractory SHPT or those unable to tolerate calcimimetics even though it results in a greater drop in PTH levels. 12,13 Furthermore, studies have demonstrated an association between severity of SHPT pre-KT and higher rates of post-KT graft failure and persistent hyperparathyroidism, also known as tertiary hyperparathyroidism (THPT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, parathyroidectomy is an effective method for long-term control, significantly lowering PTH levels into the normal laboratory reference range (<65 pg/mL) in 90%-100% of patients. 10,11 However, parathyroidectomy is typically reserved for patients with refractory SHPT or those unable to tolerate calcimimetics even though it results in a greater drop in PTH levels. 12,13 Furthermore, studies have demonstrated an association between severity of SHPT pre-KT and higher rates of post-KT graft failure and persistent hyperparathyroidism, also known as tertiary hyperparathyroidism (THPT).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, parathyroidectomy is an effective method for long-term control, significantly lowering PTH levels into the normal laboratory reference range (<65 pg/mL) in 90%–100% of patients. 10,11 However, parathyroidectomy is typically reserved for patients with refractory SHPT or those unable to tolerate calcimimetics even though it results in a greater drop in PTH levels. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the selection of a surgical approach relies on the surgeon's discretion and the clinical characteristics of the patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…PTX is an excellent long-term management strategy because it reduces PTH levels below the standard laboratory reference range in the majority of patients. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%